The Existence of Majaz Mursal in Surah Al-Baqarah from the Perspective of ‘Ilmu Al-Bayan - Lailatul Mauludiyah; Muhamad Amin; Murdiono Murdiono; Renat Sarimov (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
This study analyzed Majaz mursal contained in Surah Al-Baqarah according to Bayan Science Perspective.  Majaz mursal is part of majaz lughawi which discusses the use of lafazd not for its original meaning because there is alaqah which is in addition to likeness and there is also currynah that blocks understanding with the meaning of haqiqi (original). Research methods are libraryresearch, and data analysis techniques that use qualitative descriptive analysis techniques.   The result of this study is that "Majaz mursal in surat Al-Baqarah there are sixteen verses, namely Majaz Sababiyah is in verse 55, Musabbabiyah is in verses 174, 235, Majaz Juziyyah is found in verses 43, 112, 115, 125, 144, 177. Kuliyyah is found in verses 50, 19, Majaz I'tibaru ma'kana is not found in surat Al-Baqarah, Majaz I'tibaru maa yakuunu is found in verses 17, 49, 230, Majaz Mahaliyyah is found in verse 9, Majaz Haliyyah is found in verse 81, and Majaz Aliyah is not found in Surah Al-Baqarah.